The dark side of institutionalism: Carl Schmitt reading Santi Romano - Marc De Wilde (Ethics & Global Politics, 2018)
This article analyzes and compares the institutionalist theories of law developed by Santi Romano and Carl Schmitt. In the early 1930s, Schmitt referred to Romano to explain his own conversion to an institutionalist jurisprudence, which he preferred to call ‘concrete order thinking’. Both Romano and Schmitt criticized the normativist approach to law characteristic of legal positivism. Instead, they developed an institutionalist approach that regarded legal norms as secondary phenomena, pointing at the importance of the underlying institutional order, which shaped and informed these norms. More particularly, both Romano and Schmitt believed that the crisis of the modern state could only be overcome by recognizing the juristic character of non-state institutions and their legal orders. However, unlike Romano, Schmitt used ‘concrete order thinking’ to advocate an ideological reinterpretation of law: he thus presented the National-Socialist Führerprinzip as a ‘great example’ of ‘concrete order thinking’ and called upon German judges to reinterpret the so-called ‘general clauses’ in statutes in line with the National-Socialist ideology. While Schmitt developed ‘concrete order thinking’ into a theoretical justification of the totalitarian state, Romano emphasized the neutral and descriptive character of his institutionalist theory. Unlike Schmitt, he concluded that non-state institutions and their legal orders could never be completely incorporated into the state, but continued to exist and develop in its shadows.